Social Entrepreneurship: A New Genre of Entrepreneurship - Hossain, Mir; Shamsuddoha, Mohammad (Business Perspective Review, 2021)
Purpose: Social entrepreneurship has evolved as a domain of great significance for researchers. The positive impact of social entrepreneurship on alleviating social problems has already been proven. Traditionally, entrepreneurship has been viewed as an entrepreneur's logical response to the opportunities created by the dynamic competitive environment and thus generate profits for individuals or organizations by exploiting the opportunities. This research investigates whether social entrepreneurship is a new genré of entrepreneurship and how it differs from traditional entrepreneurship. Methods: Followed by the archive method of research, this article establishes the legitimacy of social entrepreneurship as a separate academic field and explores several factors, e.g., mission, identification, and exploitation of opportunity, and resource strategy is differentiating social entrepreneurship from its commercial counterparts. Implications: The study findings would help policymakers develop the institutional framework for supporting the social venture development process and bringing desired policy reforms to encourage social entrepreneurs' sufficient encouragement and motivation.